Bio-nanohybrids of quantum dots and photoproteins facilitating strong nonradiative energy transfer - Safak Seker, Urartu Ozgur (2016)
Utilization of light is crucial for the life cycle of many organisms. Also, many organisms can create light by utilizing chemical energy emerged from biochemical reactions. Being the most important structural units of the organisms, proteins play a vital role in the formation of light in the form of bioluminescence. Such photoproteins have been isolated and identified for a long time; the exact mechanism of their bioluminescence is well established. Here we show a biomimetic approach to build a photoprotein based excitonic nanoassembly model system using colloidal quantum dots (QDs) for a new bioluminescent couple to be utilized in biotechnological and photonic applications. We concentrated on the formation mechanism of nanohybrids using a kinetic and thermodynamic approach. Finally we propose a biosensing scheme with an ON/OFF switch using the QD–GFP hybrid. The QD–GFP hybrid system promises strong exciton–exciton coupling between the protein and the quantum dot at a high efficiency level, possessing enhanced capabilities of light harvesting, which may bring new technological opportunities to mimic biophotonic events.